Efficacy of Black Quarter Vaccine on Cattle: A Spectroscopic Approach - Rajalakshmi, A.; Renuga Devi, T.S.; Gunasekaran, S. (Asian Journal of Chemistry, 2010)
In this work, normal healthy pre vaccinated blood samples (zero day) and post vaccinated (7th, 14th, 21st day after vaccination) blood samples are analyzed by employing FTIR and UV-Vis spectroscopic techniques. The internal standards among the application peaks are calculated in both the methods. Variation is expected due to the production of antibodies in animal. Among the various techniques to study the antibody production, ELISA (enzyme-linked immuno sorbent assay) is considered a better one for the present, but it can be done only in sophisticated laboratories. Hence there is a need to try for other techniques to know the immune status of vaccinated animals. The present work can be extended and compared to the ELISA technique.